2011
DOI: 10.1002/ptr.3571
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity Against Bacteria with Dermatological Relevance and Skin Tolerance of the Essential Oil from Coriandrum sativum L. Fruits

Abstract: The aim of this work was to determine the antibacterial activity of essential coriander oil (ECO) on bacteria with dermatological relevance and to assess the skin tolerance of antimicrobial effective ECO concentrations. Essential coriander oil was tested on clinical isolates of different bacteria species, all of which may cause superficial skin infections. Antimicrobial susceptibility testing was performed using a standardized macrodilution test. Essential coriander oil showed good antibacterial activity towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…As we mentioned in the previous section, it was already demonstrated that some naturally occurring molecules have antimicrobial [137,151,153], anti-inflammatory [164,166,167] and regenerative properties [172,173,174,175,176,177,178]. From a fabrication point of view, besides the advantages already mentioned of these natural origin materials over antibiotics, their hydrophobicity allows an efficient combination with polymeric matrices often used as wound dressings [189].…”
Section: Combination Of Nanostructured Dressings With Essential Oilsmentioning
confidence: 98%
See 1 more Smart Citation
“…As we mentioned in the previous section, it was already demonstrated that some naturally occurring molecules have antimicrobial [137,151,153], anti-inflammatory [164,166,167] and regenerative properties [172,173,174,175,176,177,178]. From a fabrication point of view, besides the advantages already mentioned of these natural origin materials over antibiotics, their hydrophobicity allows an efficient combination with polymeric matrices often used as wound dressings [189].…”
Section: Combination Of Nanostructured Dressings With Essential Oilsmentioning
confidence: 98%
“…Essential coriander oil was very efficient as an antiseptic for the prevention and treatment of skin infections with Gram-positive bacteria ( Streptococcus pyogenes , S. aureus and MRSA) [153]. In addition, no skin irritation could be observed by sensitive photometric assessment in any of the 40 volunteers using patches impregnated with this essential oil.…”
Section: Essential Oils Honey Aloe Vera Cationic Peptides and Omentioning
confidence: 99%
“…No skin irritation could be observed by sensitive photometric assessment in any of the volunteers. The authors suggested that, because of its activity against Streptococcus pyogenes, Staphylococcus aureus and MRSA, with excellent skin tolerance, ECO might be useful as an antiseptic for the prevention and treatment of skin infections with Gram-positive bacteria [172].…”
Section: Coriandrum Sativummentioning
confidence: 99%
“…The seeds contain 1-2% of essential oil, which gives them flavor. Coriander EO is used as antiseptic for leather treatment against bacteria and fungi and to produce flavorings for meat products [28][29][30].…”
Section: Resultsmentioning
confidence: 99%